2020
DOI: 10.1186/s13104-020-05128-9
|View full text |Cite
|
Sign up to set email alerts
|

The current crisis of academia-led research: a threat to the common good? Preliminary data from Europe and the United States

Abstract: Objective This research note aimed to analyze the scientific productivity trends 2015–2019, focusing on the top 30 universities in Europe and United States and on the top 30 private companies—as classified in the SCImago Institutions Ranking. Our hypothesis is that private companies are gaining an increasingly prominent role in the research field, while academia is losing its predominance. Results From 2015 to 2019, all universities in Europe and the United States lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…The aim was to develop a methodology for future research. However, the results suggested that academia might lose its role in competing with internet-related private bodies which are gaining relevance [1]. These suggestions were not in agreement with the results of a recent study [3] that showed private companies not directly interested in investing in research, but rather appeared to take advantage of university research work.…”
Section: Introductioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The aim was to develop a methodology for future research. However, the results suggested that academia might lose its role in competing with internet-related private bodies which are gaining relevance [1]. These suggestions were not in agreement with the results of a recent study [3] that showed private companies not directly interested in investing in research, but rather appeared to take advantage of university research work.…”
Section: Introductioncontrasting
confidence: 65%
“…A preliminary study [1] analyzed the trends of scientific productivity from 2015 to 2019 of the top 30 private companies and top universities according to the SCImago Institutions Ranking [2]. The aim was to develop a methodology for future research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation